SISTEM AKUNTABILITAS DALAM PELAYANAN PUBLIK DI KELURAHAN PULAU KAROMAH KOTA PEKANBARU - aidil Ilham, muhammad (JURNAL KEBIJAKAN PUBLIK, 2024)
Accountability is an important principle in Good Governance. Accountability is used as a measure of bureaucratic performance in the context of providing public services. The purpose of this writing is to find out and understand the accountability of Karamah Island Village Services in 2024. This research is considered important to improve public service accountability in Pulau Karomah Village, Pekanbaru City. The research method is qualitative research with a descriptive approach. The location/place of research that will be carried out by researchers is at the Keromah Island Village Office, Pekanbaru City. The results and discussion show that there are several services that are not clear and require the community to ask sub-district officials directly regarding services that are unclear or they do not know the terms of service, and also do not include service costs in the SOP. It is also still found that there are services that do not comply with the service times that have been determined, such as in some of the cases above, such as processing poverty certificates, birth certificates and SKCK which should be completed in 10 minutes but instead are completed the next day or one day. The strategies of Karomah Island Village, Pekanbaru City in resolving the factors inhibiting public service accountability above, it can be concluded that if Karomah Island Village, Pekanbaru City is able to realize strategies including holding outreach to provide public awareness and being able to utilize the human resources it has then implementing service accountability. the public at the Karomah Island Subdistrict office, Pekanbaru City can be achieved well.